Abnormal spontaneous activity in primary myopathic disorders. Issue 3 (17th June 2017) - Nojszewska, Monika; Gawel, Malgorzata; Szmidt‐Salkowska, Elzbieta; Kostera‐Pruszczyk, Anna; Potulska‐Chromik, Anna; Lusakowska, Anna; Kierdaszuk, Biruta; Lipowska, Marta; Macias, Anna; Gawel, Damian; Seroka, Andrzej; Kaminska, Anna M.
ABSTRACT: Introduction: Reproducible non‐insertional spontaneous activity (SA), with the exception of endplate activity, is an unequivocal sign of abnormality and is one of the most useful findings obtained on electromyography. Methods: In this retrospective study we analyzed occurrence and distribution of abnormal SA in 151 patients with genetically confirmed myopathies. Results: Complex repetitive discharges (CRDs) occurred more frequently than fibrillation potentials (fibs) and positive sharp waves (PSWs) in centronuclear myopathy (CNM) and limb‐girdle muscular dystrophy type 2A (LGMD‐2A), whereas fibs/PSWs were observed more often in desminopathy and facioscapulohumeral dystrophy (FSHD). Abnormal SA was commonly found in CNM (66.7%) and desminopathy (61.5%), occasionally in Duchenne (DMD) and Becker muscular dystrophy (BMD) (45.2% and 27.6%, respectively), but rarely in FSHD (14.9%) and LGMD‐2A (12.0%). Conclusions: Abnormal SA probably occurs more frequently in disorders associated with structural changes in muscle fibers. Screening for SA may be a valuable tool for diagnosis of non‐myotonic myopathies. Muscle Nerve 56 : 427–432, 2017